GIFT TiLV Generation 20 (GIFT TiLV G20) production data - Mahmuddin, Mahirah; Hamilton, Matthew; Izadi, Fariba (2024)
Third selection of Genetically Improved Fish Tilapia (GIFT) TiLV line production data. The database categorizes 78 unique fish and includes information on their spawning date, date of fry transfer to the nursing pond, and weight in grams before and after spawning.